2011
DOI: 10.1111/j.1754-9485.2011.02304.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 10-year cause-specific mortality of patients with breast cancer treated in New South Wales in 1995

Abstract: There is no excess cardiac mortality due to RT within the first decade in a population series of patients with breast cancer treated with modern radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…Although our finding of no increase in CVD mortality among those receiving radiation therapy was in agreement with some previous studies, 33,34 this result lies in contrast to others. 9,35-39 Radiation therapy, in particular to the left side of the chest wall, may increase CVD risk through injury to cardiac muscle or the surrounding vasculature.…”
Section: Discussionsupporting
confidence: 91%
“…Although our finding of no increase in CVD mortality among those receiving radiation therapy was in agreement with some previous studies, 33,34 this result lies in contrast to others. 9,35-39 Radiation therapy, in particular to the left side of the chest wall, may increase CVD risk through injury to cardiac muscle or the surrounding vasculature.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies include patients in the era of modern radiotherapy, and the results demonstrate that the risk of cardiac-related mortality does not increase in patients receiving left-sided PORT compared to right-sided PORT, with the exception of women with a history of cardiac disease. 12 , 15 , 16 , 19 A population-based study also confirmed that the 10-year cardiac-related mortality rate in left- and right-sided tumors following PORT was only 2.4% and 1.9%, respectively, 19 which was similar to our study. However, our study also found that the risk of cardiac-related mortality steadily declined over the study period.…”
Section: Discussionsupporting
confidence: 90%
“…A total of 1 191 371 individuals were enrolled in 39 eligible studies, including 11 randomized controlled trials, 13 cancer registry database studies, and 15 single‐ and multi‐institutional trials . Twenty‐two studies were based in Europe, 13 in North America, 1 in Australia and 3 were multinational; 16 studies recruited participants from population registers, and 23 were hospital based (Table ).…”
Section: Resultsmentioning
confidence: 99%